1981
DOI: 10.1111/j.1476-5381.1981.tb09980.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of (−)‐, (±), (+)‐propranolol, Atenolol, Guanethidine, Bretylium and Tetracaine on Adrenergic Transmission

Abstract: Effects of (−)‐, (±)‐, and (+)‐propranolol, atenolol, guanethidine, bretylium and tetracaine were studied on relaxation responses of rabbit ileum and contractile responses of rabbit pulmonary artery and guinea‐pig vas deferens to electrical nerve stimulation (2 to 50 Hz) In the ileum, inhibition by tetracaine 3.3 × 10−6M occurred at high frequencies of stimulation, while bretylium 1.2 × 10−4 M and guanethidine 2 × 10−5 M inhibited responses at all frequencies, the latter producing greater inhibition at low fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…A further consequence of the interaction of propranolol with adrenergic nerve endings could be altered storage and release of noradrenaline. In animal studies, propranolol has been suggested to decrease noradrenaline release, whether by blockade of presynaptic 8-receptors (Adler-Graschinsky & Langer, 1975), a neuronal blocking effect (Saelens et al, 1977;Kaiho et al, 1981), or a central mechanism (Privitera et al, 1979). Insofar as plasma noradrenaline levels reflect the release of neurotransmitter, the data from the present study do not support diminished neurotransmitter release during treatment with propranolol.…”
Section: Discussioncontrasting
confidence: 65%
“…A further consequence of the interaction of propranolol with adrenergic nerve endings could be altered storage and release of noradrenaline. In animal studies, propranolol has been suggested to decrease noradrenaline release, whether by blockade of presynaptic 8-receptors (Adler-Graschinsky & Langer, 1975), a neuronal blocking effect (Saelens et al, 1977;Kaiho et al, 1981), or a central mechanism (Privitera et al, 1979). Insofar as plasma noradrenaline levels reflect the release of neurotransmitter, the data from the present study do not support diminished neurotransmitter release during treatment with propranolol.…”
Section: Discussioncontrasting
confidence: 65%
“…Though widely used, their mechanism of action is not fully understood. These blockers decrease the production of aqueous humor (1), but what is the pharmacological principle behind it: beta-adrenoceptor-blockade, local anaesthetic effect or adrenergic neurone blockade (2,3,4)?…”
Section: Introductionmentioning
confidence: 99%